Answer:
53q+10
Step-by-step explanation:
(-3q+3)+7(8q+1)
-3q+3+56q+7
53q+3+7
53q+10
You basically plug in the x in the equation, for example if x = 4 and the equation is y = 2x + 5 you plug in 4 and the equation becomes y = 2(4) + 5. you then multiply and get y=8+5. from here u just add it and u get ur answer
Answer:
8
Step-by-step explanation:
J'espère que cela t'aides! si c'est le cas, puis-je avoir un brainliest ?
Answer:
False
Step-by-step explanation:
Well to solve for z we single it out, distribute, use the communicative property, and combine like terms.
42 = -7(z - 3)42 = -7(z - 3)
Distribute
42 = -7z + 21*42 = -7z + 21
42 = -7z + 882 = -7z + 21
-42 to both sides
-7z + 840 = -7z + 21
-21 to both sides
-7z + 819 = -7z
+7z to both sides
819 = 0
<em>Thus, </em>
<em>the given equation is false.</em>
<em>I hope this helps :)</em>